A metafísica do belo e a tragédia em Schopenhauer - Russo, Allan Cristian Mota (2016)
We expose here Schopenhauer’s philosophy, highlighting his Metaphysics of the Beauty, wherein we demonstrate the indispensable role of the pure subject of knowledge and the genius in it. The world sometimes as the will, which is blind and source of suffering for all beings, especially humans, who have conscience and can experience like no one the dissatisfaction, the boredom and the fear of death. The world either as representation, wherein the subjectivity reigns, the phenomenon, the “veil of Maya”, in prejudice of the objectivity, that is, the thing-itself. If the asceticism way is very difficult for the humans' majority, the aesthetic way, the Metaphysics of the Beauty, it’s an affordable way, where the contemplation of Idea rises us up, even momentarily, from the misery that the world is, the “worst of all the possible worlds”. It’s a philosophy of tragedy, a tragedy that is also artistic expression, placed by our philosopher as the most exalted of representative arts, since it exposes the most terrible side of life and suggests the denial of the will, generating and uplifting empathy between the viewer and the tragic hero resigned